2021
DOI: 10.3389/fendo.2021.722441
|View full text |Cite
|
Sign up to set email alerts
|

When Leptin Is Not There: A Review of What Nonsyndromic Monogenic Obesity Cases Tell Us and the Benefits of Exogenous Leptin

Abstract: Obesity is a pandemic condition of complex etiology, resulting from the increasing exposition to obesogenic environmental factors combined with genetic susceptibility. In the past two decades, advances in genetic research identified variants of the leptin-melanocortin pathway coding for genes, which are related to the potentiation of satiety and hunger, immune system, and fertility. Here, we review cases of congenital leptin deficiency and the possible beneficial effects of leptin replacement therapy. In summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 95 publications
0
32
0
3
Order By: Relevance
“…Certain variants deposited in gnomAD and predicted to be pathogenic were previously associated with congenital leptin deficiency. The non-synonymous mutations p.Asp100Asn (rs724159998, 30), p.Asn103Lys (rs28954113, 6, 31, 32) and the frameshift mutation p.Gly133Val fs Ter15 (rs1307773933, 7) were detected in extremely obese children being homozygous carriers (5). Another study showed that BMI z-scores of carriers of homozygous LEP variants are generally higher than those of the heterozygous or wildtype individuals carrying the same variant (28).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Certain variants deposited in gnomAD and predicted to be pathogenic were previously associated with congenital leptin deficiency. The non-synonymous mutations p.Asp100Asn (rs724159998, 30), p.Asn103Lys (rs28954113, 6, 31, 32) and the frameshift mutation p.Gly133Val fs Ter15 (rs1307773933, 7) were detected in extremely obese children being homozygous carriers (5). Another study showed that BMI z-scores of carriers of homozygous LEP variants are generally higher than those of the heterozygous or wildtype individuals carrying the same variant (28).…”
Section: Discussionmentioning
confidence: 99%
“…the α-melanocyte-stimulating hormone. Eventually, the signalling of melanocortin-4-receptor is stimulated and leads to decreased food intake due to satiety signals (15).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations

Genetik

Weihrauch-Blüher,
Rajcsanyi,
Zheng
et al. 2024
Adipositas